Base-treated juniper fiber media for removing heavy metals in stormwater runoff - Min, S.H.; Eberhardt, T.L.; Jang, M. (2007)
The viability of base-treated juniper fiber (BTJF) media for removing toxic heavy metals (Cd2+, Cu2-, Pb2+, Zn2+) in stormwater runoff was investigated. The sorption ability of the BTJF for all metals was much higher than that of untreated juniper. The affinity sequence of both materials, BTJF and untreated juniper, was Pb> Cu> Zn≥ Cd. This order is explained by the hydrolysis constants for each metal. A metal desorption and column regeneration test using 0. 1 M nitric acid showed that the metal sorption capacity declined slightly from 136.3 to 119.2 μmole/g in the first two cycles and then more significantly at the third and fourth regeneration, 72.3 and 83.1 μmole/g, respectively. Based on the hydraulic conductivity test of BTJF of different size classes, it can be deduced that there is no major headloss-related disadvantage in using BTJF instead of sand as stormwater filter media if the particle size of the BTJF is similar to that for sand.